Sodium alginate hydrogel loaded with upconversion nanoparticles and magnesium ions enhances bone regeneration and photodynamic tumor therapy - Siyu Song; Siyu Song; Xirao Sun; Xirao Sun; Yanfu Wang; Meng Wang; Meng Wang; Zheng Shi; Zheng Shi; Danfang Sun; Danfang Sun; Dan Li; et al. (Frontiers in Pharmacology)
IntroductionOral squamous cell carcinoma (OSCC) usually invades the jawbone over the course of the disease. Hence, it is necessary to consider the treatment of the tumor and repair of the jawbone, and the treatment process is very complicated. However, conventional therapy for OSCC mainly emphasizes tumor removal, which often fails to address the repair of jawbone defects and destroys residual tumor cells after treatment.MethodsIn this study, we designed a composite hydrogel platform (SUMg) of sodium alginate loaded upconversion nanoparticles (UCNP) and magnesium particles (MPs), in which UCNP was coated with folic acid and chlorin e6 to prepare UFC. The physicochemical and biological properties of the prepared SUMg, including swelling test, element mapping, cell behaviors, in vivo osteogenic bioactivity and antitumor effect, were comprehensively evaluated.ResultsIn vitro, SUMg exhibited high cytocompatibility and promoted cell viability, proliferation, spreading, and osteogenesis owing to the incorporation of MPs, with SU10 Mg having the most significant effect. Under 980 nm laser irradiation, UFC induced a photodynamic therapy effect and destroyed surviving tumor cells. In vivo experiments further confirmed that SU10 Mg could promote bone regeneration, and under 980 nm near-infrared irradiation, the UFC produced local reactive oxygen species in the tumor within 5 min.DiscussionThis work demonstrated the potential of SUMg in bone regeneration and inhibition of tumor growth, providing valuable insight for OSCC treatment.